Production of Isopropyl and Methyl Esters from Yellow Mustard Oil/IPA Miscellas. (11th January 2017) - Sinichi, Sayeh; Boocock, David G. B.; Diosady, Levente L.
Abstract: Using an isopropyl alcohol (IPA):flour [volume:weight (ml:g)] ratio of 1.5:1 per stage of extraction resulted in an oil yield of 86.3%. The combined miscella (IPA + oil), which contained 90.6 wt% IPA, 9.8 wt% oil, and 2.1 wt% water, was used as a feedstock for biodiesel production by transesterification. Transesterification of the IPA/oil miscella dehydrated using adsorption on 4Å molecular sieves with 1.2 wt% (based on oil) potassium hydroxide for 2 h at 72 °C converted only 29% of the feed to esters. The addition of methanol (MeOH) resulted in an ester yield of 87%, consisting of 79% methyl ester and 7% isopropyl ester when starting with an IPA:oil:MeOH molar ratio of 146:1:30. By increasing the KOH catalyst to 3 wt%, the ester yield increased to 94%. To increase the ester yield, the miscella was pretreated with sulfuric acid. This resulted in a reduction of the IPA content, the removal of other impurities such as phospholipids, and reduction of the water mass fraction to less than 1%. When IPA was used as a cosolvent with methanol in the transesterification process, a very high ester conversion (>99%) was achieved. The biodiesel produced was compliant with ASTM standards, showing that IPA can be used as a solvent for oil extraction from yellow mustard flour.